Progress of Transfer Fund on Metro City, East Lampung Regency and Central Lampung Regency on 2022 - Royhul Akbar; Tejo Prakosa; Arien Armadiana Hutari; Iin Agustina (Jambura Equilibrium Journal, 2023)
The transferred fund 2022 consists of village funds and physical special allocation funds and Non physical special allocation funds (DAK Fisik, Non Fisik & Dana Desa), the source of funds the Central Government provides to support Regional Government Development. In 2022 in 3 Sub Regional/Local Governments within the scope of the Metro KPPN payment area, there are still obstacles to the distribution of DAK Fisik where the 3 Regions, the average Realization and Absobsion for DAK Fisik was only 97,79% 2022 of the available ceiling fund in 2022. The biggest distribution obstacle in 2022 is Recovery from the COVID-19 pandemic, leadership and world economic conditions and Russia's war with Ukraine which affected economic activity with impacts from upstream to downstream.